STUDI LITERATUR EFEKTIVITAS PEMBERIAN TANAMAN OBAT DALAM PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS - Fauziah, Fuzi (Akademi Farmasi Yarsi Pontianak, 2024)
Aim: This study aims to determine which medicinal plants and plant parts are most effective in healing perineal wounds in postpartum women and to find out information regarding the secondary metabolite content in plants which have activity in treating perineal wounds. Method: This research uses a literature study method by conducting journal searches using the Harzing's Publish or Perish application which is connected to database sources such as Google Scholar, PubMed, and Science Direct. Journal searches used the keywords